Network Management System for IoT Based on Dynamic Systems. (13th December 2021) - Alsaffar, Mohammad; Hamad, Abdulsattar Abdullah; Alshammari, Abdullah; Alshammari, Gharbi; Almurayziq, Tariq S.; Mohammed, Mohammed Shareef; Enbeyle, Wegayehu
Abstract : The Internet of Things (IoT) has the potential to transform the public sector by combining the leading technical and business trends of mobility, automation, and data analysis to dramatically alter the way public bodies collect data and information. Embedded sensors, actuators, and other devices that capture and transmit information about network activity in real-time are used in the Internet of Things to connect networks of physical objects. The design of a network management system for an IoT network is presented in this paper, which uses the edge computing model. This design is based on the Internet management model, which uses the SNMP protocol to communicate between managed devices, and a gateway, which uses the SOAP protocol to communicate with a management application. This work allowed for the identification and analysis of the primary network management system initiatives for IoT networks, in which there are four fundamental device management requirements for any deployment of IoT devices: provisioning and authentication, configuration and control, monitoring and diagnostics, and software updates and maintenance.